Public morality as a prerequisite of the scope within economic freedom term - GREßLER, MAŁGORZATA W. (Prawo Kanoniczne, 2017)
The paper approaches the problem of the public morality clause in Polish (economic) law. e use of the mentioned general clause appears to be di- cult, which seems to be conrmed by the multiple judicial decisions as well as various publications in this matter. As far as the Author’s viewpoint is concerned, it is necessary to understand the concept of “constitutional spirit” emphasizing system of Judeo-Christian values. Public morality is correlated to constitutional values order and as such is a piece of legal system in force. e national character of the clause is to be underlined. An entrepreneur is to obey public morality rules. is obedience is required by the legislator (in the Constitution and – expressis verbis – in the Economic Freedom Act).